Perceived Utility and Learning by Dominican University Students in Virtual Teaching–Learning Environments: An Analysis of Multiple Serial Mediation Based on the Extended Technology Acceptance Model - Rodríguez-Sabiote, Clemente; Valerio-Peña, Ana T.; Batista-Almonte, Roberto A.; Úbeda-Sánchez, Álvaro M. (International Review of Research in Open and Distributed Learning, 2024)
The global pandemic caused by the SARS-CoV-2 virus brought about a true revolution in the predominant teaching–learning processes (i.e., face-to-face environment) that had been implemented up to that point. In this regard, virtual teaching–learning environments (VTLEs) have gained unprecedented significance. The main objectives of our research were to define an explanatory theoretical model and to test a multiple serial mediation model with four variables in series (one independent variable plus three mediators) to relate perceived utility (independent variable) in the use of a VTLE and perceived learning (dependent or criterion variable) in such contexts, taking into account the mediation of subjective norm (mediator 1), ease of use (mediator 2), and intention to use behavior (mediator 3), and using the extended technology acceptance model as the theoretical framework. Additionally, we aimed to analyze the direct and indirect relationships and effects among the variables that constituted the proposed model. Methodologically, the research can be classified as a cross-sectional causal ex post facto design. A representative sample of students enrolled in higher education institutions in the Dominican Republic was used as the research population, and a standardized Likert scale was administered to measure the five dimensions of the proposed model. Finally, it is worth noting that the obtained results indicate that all direct and indirect effects considered in the model were statistically significant, except for the indirect effect, where the four predictor variables were arranged in series to verify their influence on the criterion variable: perceived learning.